Cognition and adaptive functioning in older people attending drug and alcohol services. (1st February 2017) - Monds, L.A.; Ridley, N.J.; Rivas, C.; Withall, A.; Draper, B.; Lintzeris, N.
ABSTRACT: Background: Substance use disorders in older adults are expected to increase dramatically in the coming years. Given the increased susceptibility to cognitive deficits in older substance users (defined here as aged 50+ years due to the accelerated health decline observed in this population), it is important to consider the functional correlates of cognitive impairment in these older adults. This study details the cognitive status of older individuals attending outpatient drug and alcohol (D&A) treatment services and seeks to determine of the association of cognitive impairment to self-reported daily functioning. Methods: Ninety nine clients aged 50 years or over attending outpatient D&A treatment services in Sydney, Australia participated. Cognition was assessed using the Addenbrooke's Cognitive Examination – Revised (ACE-R). Recent substance use (Australian Treatment Outcome Profile), physical and mental health (SF12, Geriatric Depression Scale), social isolation (Lubben Social Network Scale), and activities of daily living (Bayer ADL Scale) were also assessed. Results: Nearly two-thirds of participants screened positive for cognitive impairment on the ACE-R; 41% and 65% of clients met the cut-off scores for mild cognitive impairment (MCI) and more severe cognitive impairment, respectively. Self-reported seizure history was a predictor of cognitive impairment. Conclusions: The results suggest that cognitive impairment in this group is common. The assessment of cognitive status for this older group of patients should not only include the identification of cognitive impairment but also encompass mental health and social functioning. A greater understanding of the needs of this cohort will also enable better co-ordination with other health and welfare services tailored to this population.